A contribution to the knowledge of burrows and reproductive biology of Stenoterommata platensis Holmberg (Mygalomorphae: Nemesiidae) - Schwerdt, Leonela Vanesa (2014)
Stenoterommata platensis is a medium-sized nemesiid spider that lives in open burrows. The biology of the Nemesiidae is almost unknown. We describe the courtship and mating of S. platensis for the first time based on two observed matings and add some notes about their burrows in the wild on Martín García Island, Argentina. All males initiated courtship by beating with the first pair of legs when contacted with the female silk from the entrance of the burrow. The copulation position achieved was similar to that of most mygalomorphs. This work constitutes preliminary observations and more data are needed to a better understanding of the reproductive biology of this species.